Serviço social e ensino a distância (EAD): análise da expansão - Pimenta, Ana Cristina Borges (2009)
This research, divided into four chapters, plus the final considerations, constitutes a study of qualitative nature which tried to analyze and to develop some considerations about the dynamics of the expansion of the distance graduation courses of Social Service, grounded on the Law of Guidelines and Bases of the National Education, from 1996 to 2007, under the light of the university education reform. The paper discusses the transformations that have occurred in Brazilian higher education since the first higher education schools in Colonial Brazil until the first years of XXI century, taking into account the fact that the policy of the State towards such sector has been to play down its role. The paper starts from the principle that currently the State, on account of neoliberal and globalization policies, only adopts focalized actions and expands the opening of higher education to market forces, evidencing a trend to favor and expand privatization of the sector. With this perspective, the professional formation of the social assistant is not immune to the mercantilization of higher education, conceived with the unbridled expansion of the courses of the private higher education institutions and the novelty of the constitution and operation of the distance courses. Such scenery, taking into account the specificities of the profession, evidences a trend towards precariousness in Social Service, because of a mercantilized professional formation, compromising the quality of the Social Service teaching and creating a process of devaluation of the profession